Does Documented Brief Intervention Predict Decreases in Alcohol Use in Primary Care?. (24th August 2018) - Hepner, Kimberly A.; Hoggatt, Katherine J.; Bogart, Andy; Paddock, Susan
ABSTRACT: Background : Brief intervention (BI) is recommended for patients with unhealthy alcohol use, but the effectiveness of BI in usual care settings remains unclear. Objective : We evaluated whether BI predicts decreases in drinking 6 months after a positive screen for unhealthy alcohol use. Method : We enrolled patients who recently screened positive for unhealthy alcohol use during a routine screen in Veterans Health Administration primary care. We conducted medical record review to assess whether providers documented advice to reduce or abstain, feedback about risks to health, feedback about how patient drinking compares to norms or recommended limits, and discussion of drinking-related goals. BI elements were coded from 7 days before the date of the positive screen to 60 days after. We conducted baseline and 6-month follow-up telephone interviews to assess change in past 30-day drinking. We fit regression models examining each BI element and another model for the total count of instances of any combination of elements. Results : Of the 327 patients included, 86% had at least one documented instance of receiving advice, 86% had risk feedback, 55% had normative feedback, 38% had goal discussion, and 75% had three or more instances of any combination of elements of BI. None of the individual BI elements, nor the total number of instances, were significantly associated with decreased drinking. Conclusions : Results suggest that provider documentation of elements of BI and increasing numbers of instances of BI elements were not associated with decreased heavy drinking at 6-month follow-up among patients identified with unhealthy alcohol use.